Forecasting the Yield curve using priors from no arbitrage affine term structure models - Andrea Carriero (Queen Mary University of London, Department of Economics, 2007)
In this paper we propose a strategy for forecasting the term structure of interest rates which may produce significant gains in predictive accuracy. The key idea is to use the restrictions implied by Affine Term Structure Models (ATSM) on a vector autoregression (VAR) as prior information rather than imposing them dogmatically. This allows to account for possible model misspecification. We apply the method to a system of five US yields, and we find that the gains in predictive accuracy can be substantial. In particular, for horizons longer than 1-step ahead, our proposed method produces systematically better forecasts than those obtained by using a pure ATSM or an unrestricted VAR, and it also outperforms very competitive benchmarks as the Minnesota prior, the Diebold-Li (2006) model, and the random walk.
Keywords: C11; C53; E43; E47; 330; Bayesian methods; Forecasting; Term structure; Kapitalmarkttheorie; Zinsstruktur; Zinsstrukturtheorie; Kapitalertrag; Prognoseverfahren; Theorie